(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
contributo sottoposto a valutazione SOMMARIO: 1. Premessa – 2. Pio X e l’avvio della stagione codificatrice – 3. Collezione o codificazione? – 4. La questione sistematica – 5. Il problema dei canoni preliminari e del trattato De sacramentis. Abstract: The celebrations in the hundredth anniversary of the death of Pope Pio X, follow after a short time the thirtieth anniversary of the current Code. With this paper the Author has the aim to clarify the law thought of Pio X. His influence in the beginning of the codification process is analyzed pointing out the choice of model, collection or codex, which should assume the reformatio iuris and the framework of the his work, by the means of a critical examination of the debates among the cardinals and the councilors during the preparation of theCodex iuris canonici. The comparison among the different working groups shows the originality of the idea of the developing work and moreover of the law, especially in relation to the opportunity of planning a general part in the Code and to set systematically the treatise de sacramentis. The deep syntony between the pastoral concern of Pio X and John Paul II is clear looking at the publication of the post-Conciliar Code.